Ischemic preconditioning and nicotinamide in spinal cord protection in an experimental model of transient aortic occlusion - (:unkn) unknown (OXFORD UNIV PRESS INC, 2003)
Objectives: Spinal cord injury is a devastating complication after aortic surgery. The aim of the present study is to examine the effects of ischemic preconditioning (IPC) and nicotinamide containing perfusate in transient aortic occlusion in the rat. Methods: Thirty-two male Spraque-Dawley rats under general anesthesia were randomly assigned to four groups (n = 8 in each group). The infrarenal aortas were clamped for 45 min. Groups were as follows: Group 1, undergoing occlusion but receiving no treatment. Group 2, had 5 min of IPC before occlusion. Group 3, received nicotinamide (0.2 ml/l) during the transient occlusion. Group 4, received combined IPC (5 min) and nicotinamide infusion during the transient occlusion. The rats were then allowed for recovery and were tested for their neurological status. All animals were sacrificed at the end of the 48 It and spinal cords also examined histologically. Anti-poly (ADP-ribose) polymerase p85 fragment pAb was used as an immunohistochemical marker for detection of apoptosis. Results: In 24 h paraplegia represented as grade 0 and 1 occurred in six animals in Group 1 and two animals in Groups 2 and 3 and one in Group 4. In 48 h six animals in Group 1 and only one animal in Groups 2 and 3 showed a paraplegia. The incidence of neurologic deficit was significantly reduced in animals who had IPC and nicotinamide infusion (P < 0.05). At 48 h, combined IPC and nicotinamide showed a significant benefit compared to nicotinamide but not to the IPC alone. Histologic examination of the spinal cords revealed that a neuronal necrosis contributes to acute spinal cord degeneration after a period of aortic occlusion and both nicotinamide and IPC have protective effects against neuronal necrosis. No difference was found among the groups. Conclusions: Both IPC and nicotinamide are beneficial in protection against neurological damage in transient aortic occlusion. IPC alone as expected is significantly beneficial both at 24 and 48 h compared to controls. At 24 h combined nicotinamide and IPC show significant benefit compared to only nicotinamide, but this difference is not maintained at 48 h. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: spinal cord; aortic injury; apoptosis; INJURY; PARAPLEGIA; DEXTRORPHAN; PREVENTION; INFARCTION; RELEASE